The Impact of Working Capital, Return on Assets and Return on Equity on Corporate Income Tax - Mahardini, Nikke Yusnita (Journal of Accounting Auditing and Business, 2019)
This study aims to examine the effect of working capital, Return on Assets (ROA), and Return on Equity (ROE) on corporate income tax. The population of this study is mining companies, and the total sample was involved is thirty-six companies. The data used in the study is in the form of financial statements obtained from the Indonesia Stock Exchange (IDX). The data analysis method used in this study is the multiple regression analysis. Results of the study indicate that working capital significantly influences corporate income tax. Meanwhile, Return on Assets (ROA) and Return on Equity (ROE) are not significant to explain the variance of corporate income tax. Simultaneously, working capital, Return on Assets (ROA) and Return on Equity (ROE) as a function of corporate income tax were found significant